Maternal and perinatal results in pregnant women with COVID-19. Molina Scippa Marino Hospital 2020-2021 - León-Jacobo, Ruth Amalia (2023)
Introduction. Pregnant women are considered more susceptible to viral infections, therefore, during the pandemic they will be considered as a risk group for the development of the disease; as well as, to present obstetric complications.Objetive. To determine the maternal and perinatal outcomes in pregnant women with positive COVID-19 treated at the Hospital Marino Molina Scippa between 2020 and 2021.Materials and methods. Descriptive and cross-sectional study, 298 pregnant women with SARS-CoV-2 infection treated in the Gynecology and Obstetrics Service were included from the diagnosis of the infection until the puerperium between the years 2020 and 2021. Medical records, birth book and epidemiological records were reviewed. to collect sociodemographic, reproductive, obstetric pathology and newborn characteristics variables. The descriptive analysis was performed in SPSS v. 25.Results. The mean age of the pregnant women was 31 years, with 2.3 ± 1.3 pregnancies and a mean of 32.8 weeks of gestation, uncontrolled (55.4%) and without comorbidity (68.5%). 91.4% ended the pregnancy in delivery, 51.5% normal delivery and 39.9% cesarean section; 51.1% of the newborn (NB) was male, 91.4% with normal Apgar, normal weight (87.9%) and clear amniotic fluid (87.2%). 58.8% of newborns had late clamping of the umbilical cord, skin-to-skin contact, early breastfeeding and 72.4% had rooming-in. When the infection occurred in the I, 30.2% presented threatened abortion and 9.3% hyperemesis gravidarum, in the II trimester 24.0%Urinary tract infection (UTI) and 16.0% Threatened preterm labor (APP) and in the third trimester 12.9% UTI and 11.3% Premature rupture of the membranes (RPM). 29.4% of postpartum women had anemia, 5.7% uterine hypotonia and 1.8% uterine atony.Conclusions. The majority ended the pregnancy in childbirth (91.4%), with a healthy NB, early lactation and rooming-in. The most frequent obstetric complications were threatened abortion (I trimester) and UTI (II and III trimester).